DIAGNOSTIC SIGNIFICANCE OF KLOTHO AND CYSTATIN C IN THE EARLY STAGE OF CHRONIC KIDNEY DISEASE IN TYPE 2 DIABETES MELLITEUS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Cystatin C is a protein produced by almost all cells in the body and filtered mainly by the kidneys. It has been studied as a potential biomarker for kidney function, particularly in diabetic nephropathy, a common complication of type 2 diabetes. Klotho is a protein that has gained attention in recent years due to its potential role in various physiological processes, including kidney function and aging. Research is investigating the link between Klotho and diabetic nephropathy, especially in people with type 2 diabetes. Cystatin C and Klotho are two factors being studied in relation to the development of diabetic nephropathy in patients with type 2 diabetes. While both factors are of interest in the early diagnosis of diabetic nephropathy in patients with type 2 diabetes, they play separate roles and have different effects.